EKSISTENSI PEMBENTUKAN LEMBAGA PEMERINGKAT USAHA MIKRO KECIL MENENGAH DI INDONESIA - Darminto Hartono (Faculty of Law, Universitas Diponegoro, 2015)
This study aims to ﬁnd the institutional existence and ownership structure of credit rating agencies of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Institutional and Ownership Structure of Credit Rating Agencies MSMEs in Indonesia is conducted through the ministry of cooperatives and SMEs, the ministry of communications and information, the tourism ministry, agency securities in Indonesia, Bank Indonesia, the national banking associations, and ministries of state-owned enterprises (SOEs). Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy in Indonesia. MSMEs have a proportion of 99.99% of the total businesses in Indonesia or as many as 59.313 million of MSMEs units also prove to have contrubuted for 19.86% of the total Gross Domestic Product of Indonesia